Genome-wide meta-analysis uncovers novel loci influencing circulating leptin levels - Tuomas O. Kilpeläinen (Nature Portfolio, 2016)
This meta-analysis of genome-wide association studies identifies four genetic loci associated with circulating leptin levels independent of adiposity. Examination in mouse adipose tissue explants provides functional support for the leptin-associated loci.